Efeito da intensidade do exerc??cio nas respostas do potencial evocado e fun????o executiva de escolares do Distrito Federal - Cardeal, Cintia Mota (2014)
This study aimed to analyze the profile of executive function and neuroelectrical activations answers from the P300 component of school under acute stimuli of exercise at different intensities . The sample consisted of 60 individuals , divided randomly into control group , experimental group to the experimental group and moderate exercise to intense exercise aged 7 to 14 years . Initial tests to characterize the sample and spirometry for verification and determination of VO2max values for exercise intensity were applied . And the second time were applied cognitive tests ( Flanker and oddball paradigm ) moderate or intense physical exercise , with the reapplication of cognitive tests after acute exercise . It was observed that held moderate and intense aerobic exercise differ statistically from the control group in the executive function testing and procurement of P300. In testing the intense attention the only group differed significantly from the control group mind. In both tests the intensive group achieved better results compared to the other groups. The neuroelectrical frontoparietal network was established for the Flanker paradigm and frontoparietal network and the temporal to the oddball paradigm. We conclude that the results point to a favorable direction of physical activity in the school of moderate and intense in general.